2022
DOI: 10.1002/ctm2.893
|View full text |Cite
|
Sign up to set email alerts
|

Healthy and unhealthy plant‐based diets in relation to the incidence of colorectal cancer overall and by molecular subtypes

Abstract: Background Plant‐based foods have been recommended for health. However, not all plant foods are healthy, and little is known about the association between plant‐based diets and specific molecular subtypes of colorectal cancer (CRC). We examined the associations of healthy and unhealthy plant‐based diets with the incidence of CRC and its molecular subtypes. Methods While 123 773 participants of the Nurses’ Health Study and the Health Professionals Follow‐up Study had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 64 publications
0
9
1
Order By: Relevance
“…In contrast with our study that showed no association between hPDI and colorectal cancer risk, participants from 2 US cohorts with a higher hPDI had a significantly lower risk of colon cancer . However, point estimates for extreme quintile comparisons of 0.87 in our study and 0.86 in the US cohorts are similar, and the wider CIs in our study are likely due to the lower number of case patients (959 in the UK Biobank vs 3077 in the US cohorts).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In contrast with our study that showed no association between hPDI and colorectal cancer risk, participants from 2 US cohorts with a higher hPDI had a significantly lower risk of colon cancer . However, point estimates for extreme quintile comparisons of 0.87 in our study and 0.86 in the US cohorts are similar, and the wider CIs in our study are likely due to the lower number of case patients (959 in the UK Biobank vs 3077 in the US cohorts).…”
Section: Discussioncontrasting
confidence: 97%
“…28 In contrast with our study that showed no association between hPDI and colorectal cancer risk, participants from 2 US cohorts with a higher hPDI had a significantly lower risk of colon cancer. 29 However, point estimates for extreme quintile comparisons of 0.87 in our study and 0.86 in the US All models used age as the underlying time variable and were adjusted for sex, body mass index, race and ethnicity, physical activity level, smoking status, alcohol intake, education level, energy intake, polypharmacy index, multimorbidity index, and aspirin use, stratified by region. For myocardial infarction analyses, models were further adjusted for polygenic risk score (coronary artery disease).…”
Section: Discussionmentioning
confidence: 79%
“…Among subgroups of ultra-processed foods, higher consumption of meat/poultry/seafood-based ready-to-eat products and sugar-sweetened beverages in men, as well as ready-to-eat/heat-mixed dishes in women, is associated with an increased risk of CRC [ 27 ]. Consumption of a plant-based diet high in refined grains and sugar was associated with a high incidence of CRC [ 28 ].…”
Section: Diet and Crcmentioning
confidence: 99%
“…For instance, Diets low in milk or calcium have been identified as primary contributors to the CRC disability-adjusted life years ( 6 ). Moreover, it has been found that nutritional supplements, such as omega-3 and arginine supplementation, could also modify the risk of CRC development ( 10 ).…”
Section: Introductionmentioning
confidence: 99%